(untitled) (Práxis Educativa, 2019)
Based on the ongoing process of an action research in collaboration with young people from peripheral neighbourhoods in the city of Porto (Portugal), this article presents the results of a set of sessions of musical and theatre co-creation with two participating groups. The starting point of this collaborative research is to reflect and debate the assumption that young people do not participate politically. We also want to understand how these groups of young people can build their citizenship in the relationship with their peers and their city. Spaces of dialogue, social interaction and creative and artistic production are analysed, suggesting that these young people need to express themselves and be heard. Considering the emancipatory potentialities of the Theatre of the Oppressed and Music, one of the challenges of this study is to engage these young people as actors, co-creators and co-authors in the research about their reality and on issues affect and concern them as young citizens. Keywords: Young People. Citizenship. Collaborative Research.